Make Versus Buy in Trucking:Asset Ownership, Job Design, and Information - Baker, George P; Hubbard, Thomas N (American Economic Review, 2003)
Explaining patterns of asset ownership is a central goal of both organizational economics and industrial organization. We develop a model of asset ownership in trucking, which we test by examining how the adoption of different classes of on-board computers (OBCs) between 1987 and 1997 influenced whether shippers use their own trucks for hauls or contract with for-hire carriers. We find that OBCs' incentive-improving features pushed hauls toward private carriage, but their resource-allocation-improving features pushed them toward for-hire carriage. We conclude that ownership patterns in trucking reflect the importance of both incomplete contracts and of job design and measurement issues.